FORMULATION AND DETERMINATION OF QUALITY PARAMETERS OF PROPOLIS EXTRACT MICROCAPSULE TABLETS FROM TETRAGONULA SAPIENS - PRATAMI, DIAH KARTIKA; RAHMAT, DENI; AMALIA, RIZKA NOOR; HERMASNYAH, HERI; GOZAN, MISRI; SAHLAN, MUHAMAD (International Journal of Applied Pharmaceutics, 2022)
Objective: The study aimed to develop the dry powder of propolis microcapsules into tablet preparations. Methods: The tablet preparation was developed by direct compression method using Avicel PH 102 (filler-binder-disintegrant) with variations in Avicel PH 102 concentration of 50%, 75%, and 100%, respectively. Each of the tablets from these formulations was determined by the quality parameters of the preparation. Results: The results showed that the dry powder microcapsules had a yellow-brown powder physical form, flow time of 0.413g/second, compressibility of 18.56%, and fine powder was 80.04%. Out of the three formulae produced, formula III was the best with a tablet diameter of 11.11±0.01 mm, the thickness of 5.26±0.03 mm, disintegration time of 9.40±0.14 min, hardness of 15.46±0.84 kg/cm2, weight uniformity of 506.74±2.86 mg, friability of 0.28±0.03%. Meanwhile, Pb and Cd metal contamination were not detected, microbial contamination with Total Plate Number gave (ALT) 4.20 x 102 colonies/g, Yeast Mold Number 1.18 x 102 colonies/g, and the water content of the tablet was 5.75%. The evaluation results also showed that formula III with a 100% Avicel PH 102 concentration had a relatively better disintegration time than others. Conclusion: Propolis extract microcapsule tablet has been success developed. The best formula was used 100% Avicel PH 102 concentration.